Les trajectoires des spécialisations industrielles dans les villes petites et moyennes en France - Ivan Glita (EchoGéo)
Deindustrialization remains a key concept to describe the evolution of small and medium-sized cities. In France, industrial employment is still decreasing, especially in shrinking cities. But beyond this statement, we observe new evolutions of the spatial distribution of specialized cities. By formalizing the industrial trajectory using optimal matching methods and a specialization index, we reveal how relative specialization is preserved in small and medium sized cities, especially in some shrinking urban units, as well as in new industrial small cities.